PROPERTIES OF BOARDS MADE FROM RICE HUSK AND PORTLAND CEMENT AS BINDERS AND REINFORCED WITH SISAL FIBRES - Mrema, Alex Lyatonga (Tanzania Journal of Engineering and Technology, 2017)
A research study demonstrated that rice husks can be used to manufacture boards which can be used in low cost housing if bound by Portland limestone cement (CEM II/A-L/ 32.5R) and reinforced with sisal fibers to cater for their brittle behavior and that such boards can provide a substitute for wood panels. Boards made of rice husks and cement in the ratios of 1/3.3, 1/ 3.6 and 1/4 and with sisal fiber reinforcement contents of 0%, 0.4%, 0.5% and 0.8% were prepared and tested for their physical and mechanical properties. The results were compared with standard requirements for boards made with wood based fiber and particle panel materials according to DIN 1101 and ISO 2696 and BS EN 634-2. Results indicate that water absorption and thickness swelling decreased with an increase in fiber content and that there is an optimum rice husk/ cement ratio and fiber content that gives maximum flexural strength and that such boards could be used in low cost housing construction. The use of such boards could be seen as partially solving the problem of global warming and the problem of pollution associated with the disposal of rice husks in developing countries.